2010
DOI: 10.1002/dc.21488
|View full text |Cite
|
Sign up to set email alerts
|

Orbital aspergillus infection diagnosed by FNAC

Abstract: Fungal infections of the orbit represent a small minority of orbital infections. However, due to the virulent nature of some of the fungal species, they can have a devastating effect on ocular functions. Most of these fungi are saprophytes, which cause opportunistic infections. Aspergillus is one such fungus that can cause infection at various sites in an immunosuppressed individual. Sinonasal aspergillus infection with orbital extension and orbital aspergillus infection progress relentlessly. They can have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the eye, the main role of fibroblasts is the repopulation of acellular areas during the repair process and the regulation of inflammation during infection or surgical procedures [ 29 ]. The eye is constantly exposed to viruses, bacteria, and fungi [ 30 , 31 , 32 , 33 , 34 ], but rapid elimination mechanisms (e.g., the mechanical effect of tears and the presence of substances exhibiting microbicidal activity, such as lysozymes) often prevent the eye from becoming infected. However, alterations in the epithelial surface caused by trauma or by a decrease in the local or systemic immunological system can leave the eye vulnerable to infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, the main role of fibroblasts is the repopulation of acellular areas during the repair process and the regulation of inflammation during infection or surgical procedures [ 29 ]. The eye is constantly exposed to viruses, bacteria, and fungi [ 30 , 31 , 32 , 33 , 34 ], but rapid elimination mechanisms (e.g., the mechanical effect of tears and the presence of substances exhibiting microbicidal activity, such as lysozymes) often prevent the eye from becoming infected. However, alterations in the epithelial surface caused by trauma or by a decrease in the local or systemic immunological system can leave the eye vulnerable to infection.…”
Section: Discussionmentioning
confidence: 99%
“…We used a biopsy taken from the nasal cavity and fungal culture to confirm the diagnosis of AIFR. A study by Kurubor et al 31 confirmed the efficiency of fine-needle aspiration cytology in making an early diagnosis of AIFR.…”
Section: Discussionmentioning
confidence: 90%
“…Fine needle aspiration cytology (FNAC) is well documented as a diagnostic tool in fungal infection involving other body parts, but is not commonly performed to investigate orbital lesions. Kuruba et al [7] presented 2 cases of fungal infection of orbital and periorbital tissue diagnosed by FNAC and suggested the role of FNAC in making an early diagnosis of orbital aspergillosis, thereby allowing early therapy in these patients.…”
Section: Discussionmentioning
confidence: 99%